Peran Dan Kedudukan Wanita Dalam Perspektif Islam Dan Katolik - M. Wahid Nur Tualeka (Universitas Muhammadiyah Surabaya, 2019)
Abstract The focus of this research is to answer three fundamental problems,namely: first, what is the role and position of women in Islamic view? Secondly,what is the role and position of women in the Catholic view? Third, how aresimilarities and differences of the role and position of women in view of the tworeligions? This research is a study of literary (library research) with factualhistoricalmodels are historical facts about the role and position of women inIslam and Catholic perspective. The role and status of women here placed as anobject of research. The method used is the comparative method, comparingbetween the two legal norms and realities, both in the form of legal norms but in adifferent field, both in the form of reality. By comparing each of the aspects thatcan be formulated conclusions, along with a comparison between the two. The findings of this study: first, the Islamic equivalent to elevate womento men in general. Secondly, the Catholic Women spiritually and morally is higherthan men. Third, on the equation: 1. Both of them still maintaining responsibilityin the house of the work outside the home. 2. Both did not forbid women to workoutside the home as long as women do not necessarily let the household becomesirregular and untidy, 3. Women Muslim and Catholic alike have a role as aprotector and caregivers for their children, 4. Muslim Women and Catholicwomen also have the same inheritance rights. Differences: 1. In Islam, Charitypious and faith are equal among men with women. While the Catholic, CatholicWomen spiritually and morally higher than males. 2. In Islam, men and women,most of them are helpers and help others. They are helping each other. Whereas inCatholicism has been established that the woman was created as an auxiliaryHuman (Male). Recommendations from this study are: propaganda Islamiyah enjoiningthe good and forbidding the evil should be kept in use and never stop so the purityof Islam still exist and no loss of meaning. Allah knows best. Keywords : Catholicism, Islam, Women, Role, Position